The Role of Guidance and Counseling Evaluation: A Literature Review Study - Irfan Fauzi; Uman Suherman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to examine various literature regarding the role of evaluation of guidance and counseling. This research uses library research by searching for various relevant references (as books, journals, papers and research) related to the role of evaluating guidance and counseling in schools. The data analysis uses content analysis, namely analyzing the content of each reference obtained. The results of this research indicate that evaluation of guidance and counseling needs to be carried out as part of the professional competence of guidance and counseling teachers. Then, an evaluation is carried out in an effort to control the guidance and counseling program, and this becomes the basis for preparing the report and becomes an important note for decision making in preparing future guidance and counseling programs. This research provides a new perspective and is the basis for implementing optimal guidance and counseling evaluations in schools.